2005
DOI: 10.1007/s10680-005-3626-z
|View full text |Cite
|
Sign up to set email alerts
|

A Demographic Analysis of Registered Partnerships (legal same-sex unions): The Case of Norway

Abstract: Noack T., Seierstad A. and Weedon-Fekjaer H., 2005, A Demographic Analysis of Registered Partnerships (legal same-sex unions): The Case of Norway, European Journal of Population, 21: 89-109.Abstract. In 1993, Norway became the second country in the world to introduce registered partnerships. As with same-sex marriages, registered partnerships give the same rights and duties as marriages for opposite sex couples, with a few exceptions. The present article describes this 'new' demographic event based on Norwegia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 17 publications
1
11
0
3
Order By: Relevance
“…A first important theoretical reason to expect homogamy concerns meeting opportunities (Kalmijn, ). This is the argument most frequently used in previous literature on differences in educational and age resemblance between couples with different sexual orientations (Kurdek & Schmitt, ; Noack, Seierstad, & Weedon‐Fekjær, ; Rosenfeld & Kim, ; Schwartz & Graf, ; Solomon, Rothblum, & Balsam, ). The prevalence rates of gay men and lesbian women are considerably lower than those of heterosexual men and women, which narrows the pool of potential partners.…”
Section: Hypothesesmentioning
confidence: 92%
“…A first important theoretical reason to expect homogamy concerns meeting opportunities (Kalmijn, ). This is the argument most frequently used in previous literature on differences in educational and age resemblance between couples with different sexual orientations (Kurdek & Schmitt, ; Noack, Seierstad, & Weedon‐Fekjær, ; Rosenfeld & Kim, ; Schwartz & Graf, ; Solomon, Rothblum, & Balsam, ). The prevalence rates of gay men and lesbian women are considerably lower than those of heterosexual men and women, which narrows the pool of potential partners.…”
Section: Hypothesesmentioning
confidence: 92%
“…In most European studies, same-sex couples are shown to be less stable than their different-sex counterparts. In Norway and Sweden, for example, registered samesex partners have a higher divorce risk than different-sex married couples, even after taking relevant socioeconomic characteristics into account (Andersson et al 2006;Noack, Seierstad, and Weedon-fekjaer 2005;Wiik, Seierstad, and Noack 2014). Cohabiting same-sex couples in Britain also experience a higher dissolution rate than different-sex couples who are cohabiting or married (Lau 2012).…”
Section: Research On the Dynamics Of Same-sex Unionsmentioning
confidence: 99%
“…Our study, in contrast, overcomes this shortcoming by analyzing individuals' complete relationship histories through early adulthood. Third, most existing studies use data from same-sex cohabiting unions (Jepsen and Jepsen 2002;Lau 2012;Manning, Brown, and Stykes 2016) or married couples/registered partnerships (Andersson et al 2006;Noack, Seierstad, and Weedon-fekjaer 2005;Wiik, Seierstad, and Noack 2014). Such research faces the potential problem of differential selectivity of same-and different-sex couples into marriage or cohabitation.…”
Section: Introductionmentioning
confidence: 99%
“…De inngikk partnerskap i perioden 1993 til 2001, da fenomenet var forholdsvis ukjent, selv om den nye samlivsformen fikk mye medieoppmerksomhet. Disse tidligere studiene viste at det var en overvekt av mannlige par av dem som valgte å formalisere samlivet og at likekjønnede par, og saerlig par med to kvinner, hadde høyere skilsmisserisiko enn ulikekjønnede par (Andersson, Noack, Seierstad og Weedon-Fekjaer 2006;Noack, Seierstad og Weedon-Fekjaer 2005).…”
Section: Innledning Og Bakgrunnunclassified
“…Gjennom registeropplysninger om samtlige registrerte partnere undersøkte Noack, Seierstad og Weedon-Fekjaer (2005) …”
Section: Tidligere Studier Av Samlivsdynamikk Blant Likekjønnede Parunclassified